MicroRNAs are minor constituents of extracellular vesicles that are rarely delivered to target cells. - Manuel Albanese; Yen-Fu Adam Chen; Corinna Hüls; Kathrin Gärtner; Takanobu Tagawa; Ernesto Mejias-Perez; Oliver T Keppler; Christine Göbel; Reinhard Zeidler; Mikhail Shein; Anne K Schütz; Wolfgang Hammerschmidt (PLoS Genetics, 2021)
Mammalian cells release different types of vesicles, collectively termed extracellular vesicles (EVs). EVs contain cellular microRNAs (miRNAs) with an apparent potential to deliver their miRNA cargo to recipient cells to affect the stability of individual mRNAs and the cells' transcriptome. The extent to which miRNAs are exported via the EV route and whether they contribute to cell-cell communication are controversial. To address these issues, we defined multiple properties of EVs and analyzed their capacity to deliver packaged miRNAs into target cells to exert biological functions. We applied well-defined approaches to produce and characterize purified EVs with or without specific viral miRNAs. We found that only a small fraction of EVs carried miRNAs. EVs readily bound to different target cell types, but EVs did not fuse detectably with cellular membranes to deliver their cargo. We engineered EVs to be fusogenic and document their capacity to deliver functional messenger RNAs. Engineered fusogenic EVs, however, did not detectably alter the functionality of cells exposed to miRNA-carrying EVs. These results suggest that EV-borne miRNAs do not act as effectors of cell-to-cell communication.